Implementasi Nilai-nilai PAI dalam Kepramukaan Guna Membentuk Kecerdasan Spiritual, Intelektual Dan Emosional siswa - Abdul Muis; St Shofiyah; Muhammad Abdul Manan; Miftahul Alimin (Journal on Education, 2024)
This research aims to: 1) To describe the formation of intellectual, emotional and spiritual intelligence with PAI values. 2) To describe the implementation of PAI values ​​to form intellectual, emotional and spiritual intelligence. It is hoped that this research will enrich the body of scientific knowledge, especially regarding a method or way of forming students' spiritual, intellectual and emotional intelligence. This research is qualitative research that gets an overview of the phenomena that will be studied, both scientific and human engineering in nature, paying attention to characteristic qualities. , Data collection was carried out by conducting observations, interviews and documentation. Data analysis is carried out by giving meaning to the data that has been collected, and from that the research results can be concluded. The results of this research show (1) Forming spiritual, intellectual and emotional intelligence through the implementation of PAI values ​​(2) To implement PAI values ​​in an effort to form students' spiritual, intellectual and emotional intelligence.